THE STATE AND PROSPECTS OF DEVELOPMENT OF OILFIELD SERVICES MARKET IN RUSSIA - S. Tuktarov; O. Bolshakova (Вестник университета)
The article presents the assessment and results of researching of prospects of development of the Russian oilfield services market and Russian oilfield services companies. The analysis of the needs of the oil and gas sector in oilfield services is made. The authors consider the structure and volume of Russian market of services in oil and gas industry. Within the scope of this article the authors highlight the main problems of the oil service industry in Russia.